SINTESIS BIONANOKATALIS UNTUK PRODUKSI ASAM LEMAK SEBAGAI PREKURSOR GREEN DIESEL - Wildan Hakim, Muhammad
Diesel is the most consumed fuel in Indonesia. The search for alternative sources was carried out and obtained green diesel became the most prospective choice because it has similar properties to conventional diesel and is made from biomass. One of the method for green diesel production is by hydrolyzing vegetable oils into fatty acids before being hydrogenated. Hydrolysis of vegetable oils, lipolysis, can use lipase because of the short reaction stages and mild operating conditions. In term of lipase optimization, immobilization is the most common procedure. Therefore, this study aims to synthesize immobilized lipases in Cellulose Nanocrystals (CNCs) which produce fatty acids from olive oil. CNCs were chosen as support for lipase immobilization because they have extremely large surface area. The characterizations that are carried out in this research are crystallinity analysis of CNCs using X-ray Diffractometer, morphology imaginery of lipase/CNCs using Transmission Electron Microscope, and functional group characteristics using Fourier Transform Infrared Spectroscopy. The optimum immobilization conditions were obtained at enzyme loading of 1.5 mg, immobilization time of 2 hours, and the ratio of CNCs:EDC of 1:2.4 based on the highest enzyme activity, which was 6.72 ?mol/min.mL. At that condition was also acquired enzyme specific activity of 16,89 ?mol/min.mg with the immobilization yield of 0.56 mg lipase/mg CNCs. Afterwards, lipase/CNCs with optimum immobilization conditions have higher enzyme activity for palm oil substrate than olive oil. In addition, the thermal stability test showed the highest enzyme realtive activity was at 25oC. In lipolysis of palm oil into fatty acids, the performance of lipases/CNCs was still lower than free lipases even though it has been used 6 times.